Body_layers: a creative report by GruMa (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article-report has as main motivation to discuss the collaborative artistic processes from a collective text of the artists-researchers involved in the creation of the performance Corpo_camadas. We understand as the main contribution of this report the possibility of opening a dialogue with other artists on the challenges that arise from the elaboration of a multimedia performance, where the subject-actants, besides searching for convergences among the several languages, also need to launch themselves to the task of putting themselves personally in inventive and interpretive roles and actions that are not necessarily part of their usual enunciative practices.
Keywords: collaborative creation; creative processes; hybrid arts; artistic research; art and technology